Pengenalan Suplemen dan Makanan Fungsional untuk Atlet Basket - Nurul Ichsania; Andi Febi Irawati; Ishak Bachtiar; Irvan Sir; Irwin Irwin (Universitas Cokroaminoto Palopo, 2025)
This community service program aimed to enhance the nutritional literacy of adolescent basketball athletes through education on supplements and functional foods aligned with the physiological demands of high-intensity sports. The program employed an interactive, experience-based learning approach that actively engaged participants through material presentations, practical demonstrations, and guided discussions. Pre- and post-intervention evaluations indicated a meaningful improvement in athletes’ understanding of supplement classification, nutritional mechanisms, and the ability to assess product safety and claims. The findings highlight the importance of evidence-based nutritional education in supporting safer and more informed consumption decisions among young athletes. This program is expected to serve as a foundation for future initiatives focused on nutritional guidance and the development of healthy eating habits to support athletic performance and long-term well-being.